Validação de metodologia analítica para determinação de resíduos de fungicidas ditiocarbamatos em tomate por espectrofotometria - Leandro Augusto Ferreira de Sousa (2009)
Single laboratory validation of a spectrophotometric method using the system of vertical reaction for carbon disulfide for determination of fungicides dithiocarbamate residues in tomato, according to ISO/IEC 17025 requirements and the Brazilian legislation was accomplished. Experiments with solvent and matrix-matched calibration curves, blanks and spiked samples were performed. The assumptons related to the employed statistics were appraised and confirmed. The method linearity was obtained between 0.62 to 5.26 mg mL-1, with confirmation of the effect of the day and absence of matrix effects. The detection limit was 0.15 mg kg-1 and the limit of quantification 0.5 mg kg -1. On the quantification limit, the recovery average was 115.2%, confirming the trueness. In this level the method presented acceptable precision, with relative standard deviations of 11.82% under repeatability and parcial reproducibility conditions. The limit of decision was 2.4 mg kg-1 and the capacity of detection was 3.0 mg kg -1. The results by spectrophotometric method for determination of dithiocarbamate residues in tomato confirmed the fitness to purpose.